Role of Curcuma longa in the Management of Gingivitis - Umesh Pratap Verma; Gupta Abhaya; Sharma Disha (International Journal of Public Health Science (IJPHS), 2018)
The most prevalent form of periodontal disease is gingivitis. The bleeding on probing, erythema, edema and ulceration are important signs of gingivitis. Previously conventional periodontal therapy has relied almost exclusively upon mechanical debridement of tooth surface. But as of today conventional periodontal therapy alone is not sufficient because pathogenic bacteria has been demonstrated not only in gingival tissue but even up to the crest of alveolar bone itself. Because of the side effect of non-steroidal anti-inflammatory drug, the use of medicinal plants for treatment of this disease was advocated. Amongst the herbs, Curcuma longa belonges to family Zingiberaceae, commonly available in India and used in various domestic affairs popular as Haldi. The present study has been conducted with aims to evaluate the anti-inflammatory effect of extract of Curcuma longa as topical and irrigant in various concentrations (0.5&1%) on inflamed gingival tissue of patient with gingivitis.  All the subjects were divided into two groups.  Group one was control, Group two (Test Group) was further subdivided in to IIa and IIb. Results revealed the extract of Curcuma longa play a significant role in reducing the inflammatory response of the gingiva like reduced gingival score, bleeding on probing and probing depth.